2004
DOI: 10.1002/ajmg.a.30261
|View full text |Cite
|
Sign up to set email alerts
|

A newly recognized syndrome involving limbs, pelvis, and genital organs or a variant of Al‐Awadi/Raas‐Rothschild syndrome?

Abstract: We report on a 3-year-old Thai boy with limb, pelvic, and genital malformations. The combination of findings found in this patient is similar to that of Al-Awadi/Raas-Rothchild syndrome (AARRS) or limb/pelvis hypoplasia/aplasia syndrome. The upper limbs are more severely affected than the lower ones. Unlike that of AARRS, the radial ray is more severely affected than the ulnar ray. The presence of humeroulnar synostosis and humero-ulnar-radial synostosis and the absence of a radius distinguishes it from AARRS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The cases reported by Kantaputra and Tanpaiboon [2005] had severe femur hypoplasia but relatively well-formed hands and feet with normal nails, and were clearly not consistent with AARRS (and indeed the authors suggested a different disorder); their findings are remarkably similar to those reported as ''limb-pelvis hypoplasia/ aplasia'' by Genuardi et al [1997] (with absence of the femora but well-developed hands) and may cluster around the Schinzel phocomelia syndrome.…”
Section: Discussion Nosological Status and Diagnostic Features Of Thesupporting
confidence: 61%
“…The cases reported by Kantaputra and Tanpaiboon [2005] had severe femur hypoplasia but relatively well-formed hands and feet with normal nails, and were clearly not consistent with AARRS (and indeed the authors suggested a different disorder); their findings are remarkably similar to those reported as ''limb-pelvis hypoplasia/ aplasia'' by Genuardi et al [1997] (with absence of the femora but well-developed hands) and may cluster around the Schinzel phocomelia syndrome.…”
Section: Discussion Nosological Status and Diagnostic Features Of Thesupporting
confidence: 61%
“…Wnt10a is involved in the formation of the apical ectodermal ridge in limb buds (Narita et al 2005), but its particular role in the patterning of the skeleton is not clear. Mutations in Wnt7a have recently been shown as a primary cause of human syndromes (Woods et al 2006), collectively known as Al-Awadi/Raas-Rothschild syndrome or Schinzel phocomelia (Olney et al 2001;Kantaputra and Tanpaiboon 2005). In these congenital disorders, the pelvic girdle is either completely absent or severely malformed.…”
Section: Signals From the Paraxial Mesoderm Control Emx2 Expression Amentioning
confidence: 99%
“…The cases reported by Kantaputra and Tanpaiboon [2005] had severe femur hypoplasia but relatively well‐formed hands and feet with normal nails, and were clearly not consistent with AARRS (and indeed the authors suggested a different disorder); their findings are remarkably similar to those reported as “limb‐pelvis hypoplasia/aplasia” by Genuardi et al [1997] (with absence of the femora but well‐developed hands) and may cluster around the Schinzel phocomelia syndrome.…”
Section: Discussionmentioning
confidence: 53%